Increased genetic instability and accelerated progression of colitis-associated colorectal cancer through intestinal epithelium-specific deletion of Klf4 - Yang, Vincent W. (Mol Cancer Res, 2018)
Krüppel-like factor 4 (KLF4), a zinc finger transcription factor, regulates homeostasis of the intestinal epithelium. Previously, it was reported that KLF4 functions as a tumor suppressor in colorectal cancer. Here, evidence demonstrates that KLF4 mitigates the development and progression of colitis-associated colorectal cancer (CAC) in a murine model. Mice with intestinal epithelium-specific deletion of Klf4 (Klf4(ΔIS)) and control mice (Klf4(fl/fl)) were used to explore the role of KLF4 in the development of azoxymethane (AOM) and dextran sodium sulfate (DSS)-induced CAC. Upon AOM and DSS treatment, KLF4 expression was progressively lost in colonic tissues of Klf4(fl/fl) mice during tumor development. Klf4(ΔIS) mice treated with AOM/DSS developed significantly more adenomatous polyps and carcinomas in situ in comparison to treated Klf4(fl/fl) mice. Adenomatous polyps, but not normal-appearing mucosa, from colonic tissues of treated Klf4(ΔIS) mice contained a significantly increased number of mitotic cells with more than 2 centrosomes relative to treated control mice. KLF4 and p53 co-localize to the centrosomes in mouse embryonic fibroblasts (MEFs). Absence of KLF4 in Klf4(−/−) MEFs inhibits and its overexpression restores p53 localization to the centrosomes in Klf4(−/−) MEFs.